Pengaruh Leverage, Total Asset Turnover dan Cash Holdings Terhadap Kinerja Keuangan Sub Sektor Asuransi Yang Terdaftar di Bei Tahun 2020-2024 - Erinus Halawa; Asnahwati Asnahwati (ProBisnis : Jurnal Manajemen, 2025)
Financial performance reflects the economic results achieved by a company at a specific time through its activities. Therefore, companies are required to have a competitive advantage. Furthermore, companies are expected to improve their performance and generate maximum profits to ensure the company's survival and future development. This study used a population of 18 insurance companies listed on the Indonesia Stock Exchange (IDX) in 2020-2024. The sampling technique used was purposive sampling, which involves determining the sample based on specific considerations. In accordance with the criteria, this study used a sample of 11 companies that met the criteria set by the researcher during the study period of 2020-2024. Based on the partial study, leverage, total asset turnover, and cash holdings did not affect financial performance. However, simultaneously, holdings did not affect financial performance.